2021
DOI: 10.3389/falgy.2021.741135
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Asthma and Migraine: A Systematic Review and Meta-Analysis of Observational Studies

Abstract: Objectives: The purpose of this study was to determine the association between asthma and migraine and assess the risk for migraine in patients with asthma.Methods: We systematically searched the Cochrane Library, PubMed, Medical Literature Analysis and Retrieval System Online (MEDLINE), and Excerpta Medica dataBASE (EMBASE) databases from inception to September 26, 2021, for indexed observational studies that examined either the odds or risk of migraine in subjects with asthma. The qualities of the included s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 51 publications
(82 reference statements)
2
6
0
Order By: Relevance
“…Persons previously diagnosed with asthma were more likely to have headache than those without it. This finding supported the results of similar studies using different population‐based dataset from different countries 3–11 . For example, the Head‐HUNT study showed that asthma patients were 1.5‐fold more possibly to have headache, both migraine and nonmigrainous, than people without asthma 3 .…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Persons previously diagnosed with asthma were more likely to have headache than those without it. This finding supported the results of similar studies using different population‐based dataset from different countries 3–11 . For example, the Head‐HUNT study showed that asthma patients were 1.5‐fold more possibly to have headache, both migraine and nonmigrainous, than people without asthma 3 .…”
Section: Discussionsupporting
confidence: 84%
“…This finding supported the results of similar studies using different population-based dataset from different countries. [3][4][5][6][7][8][9][10][11] For example, the Head-HUNT study showed that asthma patients were 1.5-fold more possibly to have headache, both migraine and nonmigrainous, than people without asthma. 3 A key contribution of our study was pointing out those who had asthma attack in the past year had higher odds to have headache but emergency care visit in the past year did not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(4) Childhood allergic diseases, such as asthma, atopic dermatitis, allergic conjunctivitis, and rhinitis [24,26], were found to be associated with migraine headaches in adolescence. In addition to population-based studies, several systematic reviews and meta-analyses (not included in Table 1) have confirmed an association between asthma and migraine [61][62][63]. In a systematic review involving 389,573 participants performed to assess the overlapping risk of migraines in asthma patients and vice versa, the odds ratio (OR) of migraines in asthma patients compared with non-asthmatic individuals was found to be 1.62 (95% CI: 1.43-1.82) and migraines were associated with a significantly increased risk of asthma (relative risk (RR): 1.56; 95% CI: 1.51-1.60; p < 0.00001) [61].…”
mentioning
confidence: 99%
“…A meta-analysis of 15 published population-based studies covering a total of 1,188,780 individuals showed that migraines were associated with increased odds (OR = 1.54; 95% CI: 1.34~1.77) and risk of asthma (HR = 1.42; 95% CI: 1.26~1.60) and asthma was associated with increased odds (OR = 1.45; 95% CI: 1.22~1.72) and risk of migraines (HR = 1.47; 95% CI: 1.41~1.52) [63]. In a systematic review and meta-analysis of observational studies, including seven studies with a total of 549,534 individuals, to determine the association between asthma and migraine, asthma was also associated with increased odds (OR = 1.85; 95% CI: 1.39-2.45) and risk of migraines (RR = 1.70; 95% CI: 1.52-1.90) [62]. However, the same authors concluded that evidence associating asthma and migraine is limited [62].…”
mentioning
confidence: 99%